Method for synergistically improving electrochemical performance of lithium nickelate positive electrode material through multiple trace elements
By introducing specific trace elements into lithium nickelate cathode materials to form a coherent rock salt phase surface layer, the thermal stability and structural stability problems of lithium nickelate cathode materials are solved, their electrochemical performance is improved, and high-performance lithium-ion battery applications are realized.
Patent Information
- Application Number
- CN202511685221.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-03-17
AI Technical Summary
Existing lithium nickelate cathode materials suffer from poor thermal stability at high temperatures, severe surface side reactions, and structural collapse due to Li/Ni cation mixing defects, affecting their electrochemical performance and safety, thus failing to achieve commercial application.
By quantitatively matching three or more specific trace elements with Li and Ni, a coherent rock salt phase LixNiO(A, B, C) surface layer is formed, which suppresses structural distortion and harmful side reactions on the surface during the lithium insertion/extraction reaction.
This significantly improves the reversible specific capacity, cycle life, rate capability, and thermal stability of lithium nickel oxide cathode materials, providing a practical application pathway.
Smart Images

Figure CN121672597A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery material technology, and specifically relates to a method for improving the electrochemical performance of lithium nickel oxide cathode materials. Background Technology
[0002] Lithium-ion batteries have been widely used in consumer electronics, artificial intelligence, unmanned aerial vehicles, electric vehicles, and energy storage due to their superior performance, including high operating voltage, high energy density, and long cycle life. However, with the rapid expansion of application scenarios, further improving energy density and safety performance, while reducing manufacturing costs, remains a crucial issue that urgently needs to be addressed for the application and development of lithium-ion batteries.
[0003] Cathode materials are a key factor determining the performance and manufacturing cost of lithium-ion batteries. Layered lithium cobalt oxide cathode materials, due to their relatively low actual specific capacity, safety concerns, and the scarcity and high toxicity of cobalt resources, are mainly used in consumer electronics where energy density and cost are less critical. Layered nickel-cobalt-manganese ternary cathode materials (LiNi...) 1-x-y Co x Mn y O2 (NCM) can effectively reduce costs and has a high reversible specific capacity, enabling electric vehicles to achieve greater driving range. However, it still requires a large amount of cobalt, and its thermal stability decreases significantly with increasing nickel content. Lithium iron phosphate (LiFePO4, LFP) cathode materials have advantages such as excellent charge-discharge cycle stability, high safety, and low cost, but their energy density is low, mainly used in short-distance transportation and energy storage, and they suffer from significant capacity loss at low temperatures. Layered lithium nickel oxide (LiNiO2, LNO) cathode materials have advantages such as abundant nickel resources, high reversible specific capacity, high operating voltage, and good low-temperature performance, making them ideal next-generation lithium-ion battery cathode materials. However, pure-phase LNO products are difficult to synthesize, and the crystal structure contains unavoidable Li / Ni cation mixing defects. When charged to high voltage, irreversible phase transitions, structural collapse, oxygen evolution, and rapid cycle capacity decay occur. Furthermore, its thermal stability is poor at high temperatures, and surface side reactions are severe, thus preventing its commercial application to date.
[0004] To address the aforementioned issues, researchers have undertaken numerous effective improvements through measures such as bulk element doping, crystal structure enhancement, particle texture control, morphology design, and surface coating. Among these, the most representative NCM series ternary cathode materials, such as LiNi, have already achieved commercial application. 1 / 3 Co 1 / 3 Mn 1 / 2 O2, LiNi 0.5 Co 0.3 Mn 0.2O2 and other cathode materials. In recent years, with the rapid development of emerging industries such as electric vehicles, unmanned aerial vehicles, and robots, the market demand for high-energy-density, low-cost performance batteries has grown rapidly. Since the specific capacity of NCM ternary cathode materials increases with increasing nickel content, high-nickel NCM ternary cathode materials have become an important direction for the development of lithium-ion battery cathode materials, such as LiNi. 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.90 Co 0.045 Mn 0.045 Al 0.01 O2, LiNi 0.93 Co 0.07 Zr 0.01 B 0.01 O2 and other components have already achieved industrial applications; therefore, the nickel content in NCM ternary cathode materials is trending towards the ultimate LNO (low-NO) level. Undoubtedly, the research and development of high-performance LNO cathode materials will have excellent application prospects. Summary of the Invention
[0005] This invention provides an innovative method that, by quantitatively matching three or more specific trace elements with Li and Ni, utilizes their synergistic effect to effectively reduce Li / Ni cation mixing and residual alkali content in the crystal structure of LNO cathode materials, and induces in-situ transformation of the crystal structure on the surface to form a coherent rock salt phase Li. x A NiO (A, B, C) surface layer was used to suppress structural distortions and harmful side reactions during the lithium insertion / extraction reaction. This method significantly improved the reversible specific capacity, cycle life, rate capability, and thermal stability of LNO cathode materials, providing a feasible approach for the practical application of LNO cathode materials.
[0006] The specific steps are as follows:
[0007] According to Li 1.05-x Ni 1-y-z A x B y C zO2 (where x, y, z range from 0 to 0.05) is stoichiometrically weighed with commercially available analytical grade or battery-grade chemical reagents, nickel and lithium sources, and oxides or environmentally harmless salts or compounds containing elements A, B, and C, respectively. These are thoroughly ground or ball-milled and mixed. The resulting mixture is then placed in an atmosphere furnace, and oxygen or air is introduced. The mixture is heated to 200–550 °C at a heating rate of 2–20 °C / min and held for 0.5–15 h. Next, the mixture is heated further at a heating rate of 2–20 °C / min to 400–850 °C and held for 0.5–24 h. Finally, the mixture is cooled, discharged, and pulverized to obtain the target product. Attached Figure Description
[0008] Figure 1 This is the X-ray diffraction (XRD) pattern of the sample prepared in this invention.
[0009] Figure 2 This is a scanning electron microscope (SEM) image of the sample particles prepared in this invention.
[0010] Figure 3 This is a high-magnification transmission electron microscope (TEM) image of the surface of the sample particles prepared in this invention.
[0011] Figure 4 The sample prepared in this invention and the LNO cathode material were respectively assembled with lithium metal sheets into coin cells, and the initial charge-discharge and rate performance were measured. Wherein: Figure 4 a. The initial charge-discharge curves and coulombic efficiency of two types of coin cells were compared. Figure 4 b compared the specific capacity of two coin cells at different current rates.
[0012] Figure 5 The charge-discharge cycle performance of the samples prepared in this invention and the LNO cathode material assembled with lithium metal sheets into coin cells was measured at room temperature, high temperature, low current, and high current rate. Among them: Figure 5 a. The charge-discharge cycle performance of two coin cells at 25 °C and 1C current rate was compared. Figure 5 b. The charge-discharge cycle performance of two coin cells at 55 °C and 1C current rate was compared. Figure 5 c. The charge-discharge cycle performance of two coin cells at 25 °C and 10C high current rate was compared.
[0013] Figure 6 The charge-discharge cycle performance of the coin cell assembled with the sample prepared in this invention and commercial carbon anode material for lithium-ion batteries was measured at room temperature and 10C current rate. Detailed Implementation
[0014] Example 1
[0015] (1) Weigh 8.8964 g of nickel hydroxide (Ni(OH)2, purity ≥ 99%, analytical grade, Shanghai Bid Pharmaceutical Technology Co., Ltd.), 4.3655 g of lithium hydroxide monohydrate (LiOH·H2O, purity ≥ 99%, Aladdin Reagent (Shanghai) Co., Ltd.), 0.1989 g of aluminum hydroxide (Al(OH)3, purity ≥ 98%, Xilong Chemical Co., Ltd.), 0.2018 g of titanium dioxide (TiO2, purity ≥ 99%, Xilong Chemical Co., Ltd.), and 0.4377 g of magnesium acetate tetrahydrate (C4H6MgO4·4H2O, purity ≥ 99%, Aladdin Reagent (Shanghai) Co., Ltd.) into an agate ball mill jar, add a small amount of anhydrous ethanol, grind with a planetary ball mill for 2 h, and air dry to obtain a mixture of raw materials.
[0016] (2) Take about 5 g of the above raw material mixture and place it in a corundum boat. Put it in a tube furnace and heat it to 500 ℃ in an oxygen atmosphere at a heating rate of 5 ℃ / min and hold it for 6 h. Then, heat it to 720 ℃ at the same heating rate and hold it for 18 h. Then, let it cool down naturally to about 50 ℃, discharge the material, and grind it manually with an agate mortar for 10 min to obtain the target product M-LNTA.
[0017] a) From the instruction manual appendix Figure 1 It can be seen that the XRD spectrum of the prepared sample is consistent with the standard card (PDF#09-0063) of LiNiO2, indicating that the prepared product is an α-NaFeO2 type layered structure (space group R-3m); no impurity peaks were observed, indicating that its phase purity is high; the intensity ratio of its (003) crystal plane and (104) crystal plane diffraction peaks is 1.746, Li + / Ni 2+ The mixing rate was 2.0%, which was significantly lower than the 1.30% and 11.2% of LNO cathode materials prepared under the same conditions, indicating that its cation mixing degree was significantly reduced.
[0018] b) From the instruction manual appendix Figure 2 It can be seen that the prepared sample consists of spherical particles with a particle size of about 15 μm; the particle size of the primary particles is mainly between 0.2 and 0.5 μm, with a dense and smooth surface and almost no residual alkali.
[0019] c) As per the instruction manual Figure 3 In the sample, the interplanar spacing of the bulk phase is approximately 0.4886 nm, corresponding to the (003) crystal plane of the layered LiNiO2 crystal structure; a crystalline phase with a thickness of approximately 2 nm is formed in situ at the outer edge, with an interplanar spacing of 0.2473 nm, corresponding to the rock salt phase Li. xThe (111) crystal plane of NiO(A, B, C).
[0020] (3) Weigh 0.2000 g of the prepared M-LNTA cathode material, 0.025 g of the conductive agent acetylene black, and 0.025 g of the binder polyvinylidene fluoride (PVDF) according to a mass ratio of 8:1:1. Grind them in an agate mortar until they are evenly mixed. Add an appropriate amount of N-methyl-2-pyrrolidone (NMP) and transfer the mixture to a magnetic stirrer and stir at a constant speed for 4 to 6 hours until the slurry is free of obvious particles and stratification. Then, evenly coat the slurry onto a pre-prepared aluminum foil. Next, dry it in a forced-air drying oven at 80 °C for 12 hours until constant weight. Then cut it into small circular pieces with a radius of 0.6 cm and weigh them to obtain the M-LNTA electrode sheet. A CR2032 coin cell was assembled in an argon-filled glove box using an M-LNTA electrode as the positive electrode, a lithium metal sheet as the negative electrode, a 1.0M LiPF6 EC-DEC-EMC (volume ratio 1 / 1 / 1) solution as the electrolyte, and a ceramic-coated PP / PE porous membrane as the separator. The assembly followed the sequence of "positive electrode shell - positive electrode sheet - electrolyte - separator - electrolyte - lithium metal sheet - gasket - spring sheet - negative electrode shell". After standing for 8 hours, electrochemical performance tests were conducted.
[0021] (4) Using the LAND battery testing system (CT-2001A), constant current charge-discharge tests were performed on the assembled coin cells within a voltage range of 2.7~4.3 V:
[0022] a) At room temperature and a current rate of 0.1C (1 C = 220 mA / g), the M-LNTA electrode exhibits an initial discharge specific capacity of 223.79 mAh / g and a coulombic efficiency of 89.22%, which is superior to that of the LNO cathode material (see the instruction manual appendix). Figure 4 a) At room temperature, as the current rate increases sequentially from 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, to 10C, the specific capacitance of M-LNTA does not decrease as rapidly as that of LNO, indicating its superior high-rate performance (see the instruction manual appendix). Figure 4 b).
[0023] b) The M-LNTA electrode exhibits a discharge specific capacity of 192.6 mAh / g at room temperature and 1C current. After 500 cycles, its specific capacity remains at 121.01 mAh / g, maintaining a capacity retention of 80.34%, significantly better than the 53.37% capacity retention of the LNO cathode material (see the instruction manual appendix). Figure 5 a).
[0024] c) The M-LNTA electrode exhibits a discharge specific capacity of 198.2 mAh / g at 55 °C and a current rate of 1C. After 500 charge-discharge cycles, its capacity retention is 62.83%, significantly better than the 34.71% capacity retention of the LNO cathode material (see the instruction manual appendix). Figure 5 b).
[0025] d) The M-LNTA electrode exhibits a discharge specific capacity of 158.25 mAh / g at room temperature and a current rate of 10C. After 1000 charge-discharge cycles, its capacity retention is 47.83%, indicating good rate performance, significantly superior to LNO cathode materials (see the instruction manual appendix). Figure 5 c).
[0026] e) The M-LNTA cathode material was assembled with commercial carbon anode materials for lithium-ion batteries to form a CR2032 coin cell. After 1000 charge-discharge cycles at room temperature and a 10C current rate, the capacity retention rate was 76.28%, further demonstrating that the M-LNTA cathode material has good cycle stability and high-rate performance (see the appendix to the instruction manual). Figure 6 ).
Claims
1. A method for synergistically improving the electrochemical performance of a lithium nickel oxide cathode material by trace amounts of multiple elements, characterized in that, The specific steps are: (1) according to Li 1.05-x Ni 1-y-z A x B y C z O2stoichiometric ratio of commercially available analytical pure or battery grade chemical reagents containing Li, Ni, A, B, C element oxides or environmentally friendly salt or compound, wherein the value range of x, y, z is 0~0.05; (2) The materials taken in step (1) are ground or ball milled to fully mix and homogenize them; (3) The mixture obtained in step (2) is placed in a corundum crucible and put into an atmosphere furnace, oxygen or air is introduced, and the furnace temperature is heated to 200-550 ℃ at a heating rate of 2-20 ℃ / min, and held for 0.5-15 h; then, heated to 400-850 ℃ at a heating rate of 2-20 ℃ / min, and held for 0.5-24 h; then, cooled to obtain the target product; (4) The product obtained in step (3) is characterized by means of X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, etc. to confirm that the particle bulk layered crystal structure surface is in situ converted to form a coherent rock salt phase Li x NiO (A, B, C) surface layer, low surface residual alkali content; (5) The product obtained in step (3) is assembled into a button cell or a full cell according to the general method, and the electrochemical performance such as charge-discharge, rate, high-low temperature cycle stability and impedance is significantly improved.
2. The method for synergistically improving the electrochemical performance of lithium nickelate cathode materials by trace elements according to claim 1, characterized in that, The Li-containing substance can be lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxide, lithium chloride, lithium nickel carbonate, lithium phosphate, lithium nickelate, or other lithium-containing organic compounds (such as lithium acetate, lithium oxalate, lithium citrate, n-butyllithium, etc.).
3. The method for improving the electrochemical performance of the lithium nickel oxide cathode material by trace multi-elements synergistically according to claim 1, characterized in that, The Ni-containing substance can be nickel oxide (such as nickel hydroxide, nickel oxyhydroxide, nickel oxide, nickel sesquioxide, nickel trioxide, etc.), nickel salt (such as nickel carbonate, lithium nickelate, nickel chloride, nickel formate, nickel acetate, nickel oxalate, nickel nitrate, nickel citrate, etc.), or other nickel-containing compounds (such as nickel nitride, nickel carbide, nickel hydride, etc.).
4. The method for improving the electrochemical performance of a lithium nickel oxide cathode material by trace amounts of multiple elements synergistically according to claim 1, characterized in that, The A-containing substance can be a salt or compound containing K, Na, Ca, Mg, Ag, Zn, etc., or a part of them is used in a certain proportion.
5. The method for improving the electrochemical performance of the lithium nickel oxide cathode material by trace multi-elements synergistically according to claim 1, characterized in that, The B-containing substance can be a salt or compound containing Ti, Ta, Nb, W, Mo, V, Sn, Sb, etc., or a part of them is used in a certain proportion.
6. The method for improving the electrochemical performance of a lithium nickel oxide cathode material by trace amounts of multiple elements synergistically according to claim 1, characterized in that, The C-containing substance can be a salt or compound containing Al, Zr, La, Ce, B, etc., or a part of them is used in a certain proportion.
7. The method for improving the electrochemical performance of a lithium nickel oxide cathode material according to claim 1, wherein, The A, B, and C elements generally do not contain Co and Ni elements used in ternary positive electrode materials of lithium ion batteries; if introduced due to raw material sources or other reasons, the atomic ratio of Co and Mn should be strictly controlled to be below 0.
05.
8. The method for synergistically improving the electrochemical performance of lithium nickelate cathode materials by trace elements according to claim 1, characterized in that, The Li, Ni, A, B, and C raw materials can be used to prepare precursors containing these elements by wet chemical methods, or precursors containing part of these elements, such as carbonates, oxalates, acetates, hydroxides, oxides, and other multi-element mixtures.
9. The method for synergistically improving the electrochemical performance of lithium nickelate cathode materials by trace elements according to claim 1, characterized in that, The raw material mixing step can use manual or mechanical mixers to mix the raw materials uniformly in one step or gradually, or use water, ethanol, or other inexpensive liquids as solvents or dispersants to mix the raw materials uniformly.
10. The method for improving the electrochemical performance of a lithium nickel oxide cathode material by trace amounts of multiple elements synergistically according to claim 1, characterized in that, The heating and holding reaction step, the heating rate, holding time, calcination stage, and cooling system are determined comprehensively according to the type and nature of the raw materials, the degree of reaction completion, the crystal structure of the material and the growth of surface crystals, and the electrochemical performance of the target product.